Multicolored silver nanoparticles for multiplexed disease diagnostics: distinguishing dengue, yellow fever, and Ebola viruses1. Issue 7 (7th April 2015) - Yen, Chun-Wan; de Puig, Helena; Tam, Justina O.; Gómez-Márquez, José; Bosch, Irene; Hamad-Schifferli, Kimberly; Gehrke, Lee
<x xml:space="preserve">Abstract</x> Multicolor silver nanoparticles enable multiplexed detection of dengue, yellow fever, and Ebola virus proteins in a single lateral flow strip.